Effects of TEACCH Model towards the Eating Skills on Student with Autism - Lia Ayuning Tiasari; Mohammad Efendi; Ahmad Samawi (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2020)
The purpose of this research is to describe the influence of the TEACCH method towards the eating skills of a grade III Student with autism. The research used the experimental method with Single Subject Research (SSR) with the A-B-A design models. The subject in this study was a 12 year old who had barriers in communication, interaction, behavior and regulate emotions. The instruments used in the form of observational checklist compiled based on task analysis in the form of an assessment rubric. The result of study was the effect TEACCH method of influence on the ability of the eating skills of student with autism at grade III..